Evalution the effect of educational programs and facilities on interns\' satisfaction with their professional capabilities in the cardiology department of Babol University of Medical Sciences - Mohammad Ali Qasemi Darzi; Mehrdad Saravi; Hemmat Gholinia; Fatemeh Jafarian (آموزش پزشکی)
Background and Objective: Considering the importance of appropriate training of medical students to improve their professional abilities to high levels, in this study, we decided to examine the impact of the educational program on the satisfaction of interns with their professional competence in the educational department of cardiovascular diseases Methods: During this study, the interns entered the study after checking the entry and exit criteria, and then they were asked to answer the questionnaire made by the researcher, the required information along with the demographic information was collected and analyzed. Findings: 153 participants were included in the study, the average age of subjects was equal to 25/39 ±24/1 and 48/4% were men and 51/6% were women. The results indicated that the educational program was unrelated to participants' age, gender, or grade point average, but significantly impacted their professional ability. (p-value<0.05). Conclusion: This study showed that to achieve the desired professional capability, it is necessary to pay special attention to the effective factors, especially the training program, and by developing a suitable training program, the professional ability of interns can be improved